Dietary requirement of the Indian major carp, Catla catla for the essential amino acid lysine - Satheesha, S K; Murthy, H Shivananda (The Indian Journal of Animal Sciences, 2012)
Qualitative and quantitative dietary requirement of Catla catla juveniles for the essential amino acid (EAA), lysine, was studied by conducting a growth study. Diets incorporating casein and gelatin, as sources of intact protein supplemented with crystalline amino acids were formulated to a crude protein content of 35%. Diets with 6 graded levels of lysine (3.00, 3.93, 4.83, 5.80, 6.77 and 7.71% of protein) were formulated and fed to triplicate groups of juvenile catla 4 times a day up to satiation for 60 days. Dissolved oxygen, pH, total ammonia and free carbon dioxide were monitored every week. Optimum dietary requirement of catla for lysine as determined by break point regression analysis was 2.4% of diet, which corresponds to 6.86% of dietary protein. Growth rate, food conversion rate, specific growth rate and survival were better in catla fed with diets containing 2.4% lysine.